Photoacoustic characterization of CuSe metal chalcogenide semiconductor using phase signal analysis - Liew, Josephine Ying Chyi; Talib, Zainal Abidin; Mat Yunus, Wan Mahmood; Zainal, Zulkarnain; Shaari, Abdul Halim; Lim, Kean Pah; Abd. Moksin, Mohd Maarof; Wan Yusoff, Wan Mohamad Daud (Malaysian Institute of Physics, 2008)
Open photoacoustic cell analysis has been done on CuSe metal chalcogenide semiconductor to obtain thermal and carrier transport properties. The thermal diffusivity, carrier diffusion coefficient, surface recombination velocity and recombination lifetime of the CuSe were determined from the photoacoustic phase signal-frequency analysis. The experimental results show that the surface recombination velocity decreases with the increasing of CuSe sample thickness. The results indicate an increasing trend of band-to-band recombination lifetime in conjunction with the increasing of sample thickness.